Between Political Legitimacy and Social Fabric of Society: Imamite-Shiite Interpretation of Qur’anic Verse 16: 90 - Asfa Widiyanto (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2021)
This paper investigates the dialectics between “political legitimacy” and “social fabric of society”, as it develops in the Imamite-Shiite Qur’anic commentaries on Qur’anic verse 16: 90. It reveals the transformation and development of Imamite-Shiite exegesis pertaining to Q. 16: 90, ranging from classical to modern. It takes into a closer look into seven Qur’anic commentaries which may serve as examples of different typologies within Imamite-Shiite exegetical tradition. It argues that the Imamite-Shiite interpretation on this verse moves between these two poles (political legitimacy and social fabric of society) most notably due to the religious and political circumstances of the exegetes. From these Quranic commentaries, one may also notice the division and ecumenism between Sunnism and Shiism. This paper underlines a colourful nuance of Shiite exegesis and denies the simplified belief that Shiite exegesis is sectarian.